Analisis Numerik Rembesan dan Analisis Geofisika Dam Ranu Klakah: Seepage Numerical Analysis And Geophysics Analysis Of Ranu Klakah Dam - Assajjad, Nurrohman Adi; Asmaranto, Runi; Cahya, Evi Nur (Universitas Jember, 2024)
Abstract Ranu Klakah Dam is an old weir that is indicated to have seepage in its downstream section. The purpose of this study is to numerically analyze seepage that occurs due to piping at Ranu Klakah Dam, including the potential location of seepage points. Geophysical analysis was conducted to visually see the seepage position on the body of Ranu Klakah Dam so that appropriate repairs could be made. Numerical analysis was conducted with the help of the Geostudio SEEP/W application, while geophysical analysis was conducted using ADMT geoelectric and ground-penetrating radar tested at the research location to interpret the subsurface layer. From the analysis, we obtained a seepage discharge of 4.38 x 10-8 m3/dt, which is still smaller than the permitted seepage discharge of 1% of the average river discharge of 0.131 m3/dt. The value of the safety factor for piping in 5 m high water level conditions is 5.01 > 4, which is the limit of the safety value. From the results of the geophysical analysis, it is known that the seepage zone is located at the baffle pillar building between the flushing door and the sluice gate at a distance of about 6–8 m from the vehicle floor on the bridge above the gate, so that repairs can be focused at this point. Thus, seepage that occurs due to piping downstream still meets the established safety requirements. Keywords: Geoelectric, Ground Penetrating Radar, piping, seepage. Abstrak Dam Ranu Klakah merupakan bendung lama yang terindikasi terjadi rembesan pada bagian hilirnya. Tujuan dari studi ini adalah menganalisa secara numeris rembesan yang terjadi akibat piping pada Dam Ranu Klakah, termasuk potensi lokasi titik rembesan. Analisa geofisika dilakukan untuk dapat melihat secara visual posisi rembesan pada tubuh Dam Ranu Klakah, untuk dapat dilakukan perbaikan secara tepat. Analisa numerik dilakukan dengan bantuan aplikasi Geostudio SEEP/W, sedangkan analisa geofisika dilakukan dengan menggunakan Geolistrik ADMT dan Ground Penetrating Radar yang diujikan pada lokasi penelitian guna menginterpretasi lapisan bawah permukaan. Dari analisa yang dilakukan, didapatkan hasil debit rembesan sebesar 4,38 x 10-8 m3/dt, yang nilainya masih lebih kecil dari debit rembesan yang diizinkan sebesar 1% dari debit rata-rata Sungai yakni sebesar 0,131 m3/dt. Nilai faktor keamanan terhadap piping untuk kondisi muka air setinggi 5 m yaitu 5,01 > 4, sebagai batas nilai keamanan. Dari hasil analisa geofisika, diketahui zona rembesan terletak pada bangunan pilar penyekat antara pintu pembilas dengan pintu air sekitar jarak 6 – 8 m dari lantai kendaraan pada jembatan di atas pintu, sehingga perbaikan dapat difokuskan pada titik ini. Dengan demikian, rembesan yang terjadi akibat piping pada bagian hilir, masih memenuhi syarat keamanan yang ditetapkan. Kata kunci: Geolistrik, Ground Penetrating Radar, piping, rembesan.